التناص مع الأمثال الشعبية في روايتي القاهرة الجديدة وحضرة المحترم لنجيب محفوظ - Mohd Azizul Rahman Zabidin; Ebrahim Mohammad Ahmad Eldesoky; Lubna Abd. Rahman (PENERBIT UNIVERSITI SULTAN ZAINAL ABIDIN, 2024)
Non-Indexed Publication